Strategi Kepala Sekolah Dalam Meningkatkan Karakter Siswa Di Sekolah Menengah Pertama Kecamatan Situraja - Yuli Sintanawati; Cepi Triatna; Cicih Sutarsih (BRILIANT: Jurnal Riset dan Konseptual, 2026)
This research is motivated by the declining character of students in junior high school. This study aims to analyze and describe the principal's strategy in improving student character in junior high schools in Situraja District. Using a qualitative approach with descriptive method. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies. The results showed that the principal's strategy in improving student character includes: Development of religious habituation programs and positive school culture, Strengthening cooperation with parents and communities, Implementation of integrated character mentoring programs, and Optimization of character values-based extracurricular activities. These programs have proven effective in improving student character. The conclusion of this study reveals that the success of student character building is highly dependent on the principal's visionary leadership and the consistency of program implementation. The implications of this study emphasize the importance of developing principals' competencies in designing contextual and sustainable character-building programs, as well as the importance of building a character education ecosystem that involves all education stakeholders.